AFFIXED REDUPLICATION FORMING DEVERBAL NOUN IN JAVANESE LANGUAGE - Nanik Herawati (Universitas Sebelas Maret, 2017)
The goal of this research are (1) to describe affixed reduplication forming deverbal noun, and (2) to describe the meaning of affixed reduplication forming deverbal noun. This research uses theory about (1) morphology, (2) affixed reduplication, (3) derivation, (4) words, (5) nouns, and (6) verbs. Methodology used in this reseach is stuctural description. Research data are affixed reduplication words forming deverbal noun in Javanese language. Data collecting is done by observation, interview, and documen analysis. Data collecting method are scrutinicing and interviewing method. The result of this study is affixed reduplication -an forming deverbal noun. (reduplication -an -R -an). The meaning of this reduplication is ‘producing something like the basic form of the word.